1996
DOI: 10.1007/bf02261776
|View full text |Cite
|
Sign up to set email alerts
|

Physical mapping of repetitive DNA sequences and 5S and 18S–26S rDNA in five wild species of the genusHordeum

Abstract: The genetic relationships between several wild species and subspecies of the genus Hordeum were assessed using fluorescence in situ hybridization (FISH). Plant material included natural populations of wild barley growing in Spain of the annual species, H. marinum ssp. marinum (2n = 14) and gussoneanum (2n = 14), and H. murinum ssp. murinum (2n = 28), and leporinum (2n = 28) and the perennial species H. bulbosum (2n = 14) and H. secalinum (2n = 28), plus the South American perennial species H. chilense (2n = 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 52 publications
3
38
0
1
Order By: Relevance
“…2). These results generally confirm the previous reports of rDNA patterns in diploid cytotypes of H. marinum (Bustos et al 1996, Taketa et al 1999a). The tetraploid cytotype of ssp.…”
Section: Rdna Mappingsupporting
confidence: 93%
See 1 more Smart Citation
“…2). These results generally confirm the previous reports of rDNA patterns in diploid cytotypes of H. marinum (Bustos et al 1996, Taketa et al 1999a). The tetraploid cytotype of ssp.…”
Section: Rdna Mappingsupporting
confidence: 93%
“…In Hordeum, ribosomal DNA sites are excellent chromosome markers to study phylogenetic relationships of species (Bustos et al 1996, Taketa et al 1999a, 2001, 2005. Both classes of rDNA sites are known to evolve dynamically, and our interpretation assumes that all rDNA sites are generally conserved in these species.…”
Section: Rdna Mappingmentioning
confidence: 94%
“…An alloploid origin of the tetraploid cytotype ssp. murinum 4x has been suggested by several cytological studies based on its C-banding pattern (LindeLaursen et al 1989) and rDNA sites (Bustos et al 1996, Taketa et al 1999b. Moreover, in situ hybridization analyses using repetitive DNA sequences as probes suggested that ssp.…”
Section: Analyses Of Tetraploid Cytotypes In H Marinum and H Murinummentioning
confidence: 98%
“…These methods resulted in detailed karyograms of Hordeum species (Linde-Laursen et al 1992) and allowed the formulation of evolutionary hypotheses about species relationships (Linde-Laursen et al 1995 and references therein). I here shortly review advances in karyology with special emphasis on in situ hybridization methods introduced during the last two decades in Hordeum research (e.g., Leitch and Heslop-Harrison 1992, De Bustos et al 1996, Taketa et al 1999a, 2000b, and their special relevance to complement phylogenetic analyses in the genus.…”
Section: Cytological Analyses Within Hordeummentioning
confidence: 99%
“…FISH helps particularly to define the occurrence of rDNA tandem repeats on specific chromosomes, thus making (i) chromosome recognition much easier and (ii) allows also inference of the number of independent rDNA loci within a chromosome (e.g., Leitch and Heslop-Harrison 1992, De Bustos et al 1996, Taketa et al 2001. GISH data are quite helpful in the analysis of polyploids.…”
Section: Cytological Analyses Within Hordeummentioning
confidence: 99%